Analysis of eccentrically loaded FRP partially wrapped reinforced concrete columns subjected to combined environmental erosion. (1st April 2023) - Gu, Zhiqiang; Wei, Congjie; Wu, Chenglin; Gao, Danying; You, Peibo; Wei, Dong
Highlights: The behavior of eccentrically loaded FRP partially strengthened column was studied. Both the chloride and freeze–thaw erosion were applied to the columns. The load capacity of columns firstly increases and then decreases with the increasing corrosion degree. A simplified analytical model to predict the ultimate bearing capacity of columns was developed. Abstract: The behavior of eccentrically loaded fiber reinforced polymer (FRP) partially wrapped reinforced concrete (RC) columns under combined environmental erosion was investigated in this paper. Circular RC columns were firstly subjected to chloride erosion where the target corrosion degree (0, 10 %, and 20 %) is obtained with externally applied current. This was then followed by partially strengthening with 2-ply of glass fiber reinforced polymer (GFRP) strips as well as 50 freeze–thaw cycles. Series of eccentric compression tests were conducted with ranging eccentricities of 0, 5 mm, 10 mm, and 15 mm. For comparison, the carbon fiber reinforced polymer (CFRP) partially strengthened columns with the corrosion degree of 10 % and subjected to 50 freeze–thaw cycles were also eccentrically loaded with an eccentricity of 10 mm. Results showed that with increasing corrosion degree, the bearing capacity of GFRP strengthened column showed a 2-stage behavior (firstly increased and then decreased), which may be caused by the confinement reduction of FRP on columns due to severe environmental erosion. Under small eccentric loading, The CFRP strengthened RC columns showed better compressive behavior than that of GFRP strengthened RC columns. Based on the stress–strain relationship of constituent materials, a simplified analytical model considered the effects of chloride and freeze–thaw erosion was put forward to predict the bearing capacity of FRP partially wrapped RC column under eccentric loading.